Uncovering the Power of Educational Websites as a Means of English Language Learning: Students’ Perspective - Sherly Desliyanah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Technology is essential to the efficient teaching and learning process. But technological advancement does not ensure that everyone can take full use of it. Acquiring technical literacy or knowing how to utilize it involves more than just learning how to read; it also involves being able to use, access, and integrate technology into the teaching and learning process. Although a lot of people use the internet, not everyone is able to fully utilize its benefits, particularly in the field of education. Learning can be done more quickly and in a number of ways, particularly while learning English. In our nation, English is a foreign language, and students will have a lot of trouble using it. Therefore, in order to help students understand and avoid becoming disinterested in the process of learning English, teachers need to possess additional skills. As a result, providing the internet and educational websites as resources for learning English will benefit both educators and learners. While the use of the internet for educational purposes is not new in our nation, not all institutions are able to put it into practice because of a lack of necessary resources, including computer equipment and internet access.